Identification for Development : Sierra Leone - World Bank (World Bank, Washington, DC, 2017)
The Government of Sierra Leone (GOSL) has developed an ambitious plan in 2014 to reform civil registration in the country and to establish a national identity register. About 5 percent of people in Sierra Leone are registered in a national identity registry, managed by the National Registration Secretariat (NRS). The development of digital identity in Sierra Leone can help the country’s economic and social development. The use of an official identity can improve the efficiency and reduce the cost of collecting taxes, conducting census, issuing passports, delivering pensions, managing elections, controlling borders, delivering financial services, and running effective safety net programs. This report provides a rapid diagnosis of the potential and readiness of digital identity in Sierra Leone, and is funded by the Korean Trust Fund (KTF) and the Ebola multi-donor trust fund (MDTF). The report is based on consultations held with the GOSL and with stakeholders in the identity ecosystem of Sierra Leone. The report provides a preliminary review of the enabling environment and the functional identity programs in Sierra Leone, along with a discussion of possible next steps.